2012
DOI: 10.1001/jama.2012.40
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity and Trends in Body Mass Index Among US Children and Adolescents, 1999-2010

Abstract: Context The prevalence of childhood obesity increased in the 1980s and 1990s but there were no significant changes in prevalence between 1999-2000 and 2007-2008 in the United States. Objectives To present the most recent estimates of obesity prevalence in US children and adolescents for 2009-2010 and to investigate trends in obesity prevalence and body mass index (BMI) among children and adolescents between 1999-2000 and 2009-2010. Design, Setting, and Participants Cross-sectional analyses of a representative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

91
2,734
23
59

Year Published

2012
2012
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,459 publications
(2,907 citation statements)
references
References 28 publications
91
2,734
23
59
Order By: Relevance
“…In the United States, the Centers for Disease Control and Prevention (CDC) estimates that childhood obesity affects 17% of all children and adolescents, a rate which has tripled from one generation ago. [3][4][5] The United Nations (UN) recognizes that reducing obesity requires urgent global action and has responded with policies and procedures that require the involvement of stakeholders from many sectors (such as health, education, nutrition, policy, agriculture, industry and trade, finance) to combat this epidemic. 1 The UN realizes that childhood obesity will only be resolved with a combination of interventions catering to the specific needs of the geographic area and population receiving the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, the Centers for Disease Control and Prevention (CDC) estimates that childhood obesity affects 17% of all children and adolescents, a rate which has tripled from one generation ago. [3][4][5] The United Nations (UN) recognizes that reducing obesity requires urgent global action and has responded with policies and procedures that require the involvement of stakeholders from many sectors (such as health, education, nutrition, policy, agriculture, industry and trade, finance) to combat this epidemic. 1 The UN realizes that childhood obesity will only be resolved with a combination of interventions catering to the specific needs of the geographic area and population receiving the intervention.…”
Section: Introductionmentioning
confidence: 99%
“…However, increasingly, low energy density foods such as fresh fruit and vegetables are being replaced by high fat, high sugar, snack, drink and meal products, which may lead to increased obesity and its related disorders (Kaufman, 2002). In the USA alone, it is suggested that the number of obese 6-11 year old children has increased from 7% in 1980 to nearly 18% in 2010 (Ogden, Carroll, Kit & Flegal, 2012); and that fewer than one in five children between the ages of 4-13 are consuming the recommended five or more daily portions suggested (Guenther, Dodd, Reedy & Krebs-Smith, 2006). In the UK, the Department of Health (2013) reports that almost 30% of children between the age of 2 and 15 are now obese.…”
Section: Introductionmentioning
confidence: 99%
“…Sugary drinks are the number one source of added sugar in Americans' diets (2) and a child's likelihood of becoming obese increases by 60 % for every 8 fl oz (237 ml) sugary drink consumed per day (4) . Further, concerning health outcomes related to added sugar consumption, including obesity and type 2 diabetes, are increasing for youth (5)(6)(7)(8)(9)(10)(11) . These health trends are particularly troubling in light of evidence that dietary habits and overweight status in childhood and adolescence are strong predictors of future health (12)(13)(14) .…”
mentioning
confidence: 99%